2010
DOI: 10.1002/humu.21138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel truncated androgen receptor (AR) mutants including unreported pre-mRNA splicing variants in the 22Rv1 hormone-refractory prostate cancer (PCa) cell line

Abstract: Advanced prostate cancer (PCa) has emerged as a public health concern due to population aging. Although androgen deprivation has proven efficacy in this condition, most advanced PCa patients will have to face failure of androgen deprivation as a treatment. Mutations in the androgen receptor (AR) from tumor cells have been shown to induce androgen independency both in PCa cell lines and in the clinic. We have investigated the molecular events leading to androgen independency in the 22Rv1 cell line, a commonly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 14 publications
(22 reference statements)
3
65
0
Order By: Relevance
“…Compared with LNCaPs, 22Rv1 cells secrete low levels of PSA and express lower levels of AR, which also harbors a rare H874Y mutation (Table 2; Attardi et al 2004). In addition, 22Rv1 cells harbor two AR forms, a larger one expressing three zinc finger motifs due to duplication of exon 3 and a C-terminally truncated, constitutively active form, both of which have been functionally investigated by a number of groups (Dehm et al 2008, Guo et al 2009, Marcias et al 2010, Watson et al 2010, Dehm & Tindall 2011. Consequently, 22Rv1 has become a valuable model system to study AR function, the efficacy of existing drugs and to design novel anti-AR therapies that also target nontruncated regions of AR (Laschak et al 2012, Li et al 2012b.…”
Section: Cell Lines Established From Xenotransplanted Tumorsmentioning
confidence: 99%
“…Compared with LNCaPs, 22Rv1 cells secrete low levels of PSA and express lower levels of AR, which also harbors a rare H874Y mutation (Table 2; Attardi et al 2004). In addition, 22Rv1 cells harbor two AR forms, a larger one expressing three zinc finger motifs due to duplication of exon 3 and a C-terminally truncated, constitutively active form, both of which have been functionally investigated by a number of groups (Dehm et al 2008, Guo et al 2009, Marcias et al 2010, Watson et al 2010, Dehm & Tindall 2011. Consequently, 22Rv1 has become a valuable model system to study AR function, the efficacy of existing drugs and to design novel anti-AR therapies that also target nontruncated regions of AR (Laschak et al 2012, Li et al 2012b.…”
Section: Cell Lines Established From Xenotransplanted Tumorsmentioning
confidence: 99%
“…In a ligand-independent manner, AR isoforms promote the expression of endogenous ARdependent genes, as well as the proliferation of 22Rv1 cells. However discordant finding was given by Marcias et al (41), who documented a variant. 22Rv1 cells also express a mutant AR lacking exon 3 tandem duplication, doubtlessly, a major feature of this cell line.…”
Section: Androgen Receptor Infrastructure: Marching To a Different Drmentioning
confidence: 82%
“…Interestingly, AR3 protein was demonstrated largely in cytoplasm, however, experimental evidence showed that AR3 could act as a transcription factor via an ARE of AR regulated genes and promote cell proliferation in the absence of androgens. In addition to the variants identified in the above studies, a group of investigators (Marcias et al, 2010) recently also identified several novel constitutively active AR variants in this same CWR22R cell line, which were generated by aberrant pre-mRNA splicing or nonsense mutations. It will be interesting to determine if these new variants are frequently expressed in clinical specimens.…”
Section: Ar Variants or Splicing Isoforms In Crpcmentioning
confidence: 90%